Synchronous gastrointestinal stromal tumour and neuroendocrine tumour in a patient with neurofibromatosis type 1: a rare clinical association - Hiremath, Ashwini C.; Satyanesan, Jeswanth; Lakshmanan, Anand; Kumar, Senthil (International Surgery Journal, 2026)
Type 1 Neurofibromatosis (NF1) is an autosomal dominant disorder caused by germline mutation of the NF1 gene. While it typically manifests as multiple cutaneous neurofibromas and café-au-lait macules, patients also have an inherent predisposition to neoplasms arising from neural crest–derived tissues and the gastrointestinal tract. GISTs are relatively well-recognized in NF1, whereas neuroendocrine tumours (NET) are uncommon. The synchronous occurrence of both NET and GIST in an NF1 patient is exceedingly rare. We present a 53-year-old female with known NF1 who developed synchronous small-bowel GIST and pancreatic NET. The patient presented with intermittent jaundice. Imaging suggestive of periampullary carcinoma. During Whipple’s procedure, lesions suggestive of periampullary carcinoma and small bowel GIST were identified. Both tumours were resected. Histopathology confirmed high grade spindle-cell GIST and well-differentiated NET. The postoperative course was uneventful. NF1-associated GISTs are not uncommon, but coexistent NETs are rare and easily overlooked. This case underscores the need for heightened vigilance and a broadened differential diagnosis in NF1 patients presenting with gastrointestinal symptoms, as synchronous multifocal tumours may be missed without careful evaluation.